Epigenetics and Behçet’s Disease: DNA Methylation Specially Highlighted - Jafar Farhadi; Mohammad Nouri; Ebrahim Sakhinia; Nasser Samadi; Zohreh Babaloo; Shahriar Alipour; Golamreza Jadideslam; Farhad Pouremamali; Alireza Khabbazi (Iranian Journal of Allergy, Asthma and Immunology, 2019)
Behçet's disease (BD) is a multisystem inflammatory disease with unknown etiology. Although evidence about the pathogenesis of BD is growing, the actual cause of this disease is unclear. Both genetic and epigenetic factors are claimed to play significant roles in BD. Epigenetic factors such as age, gender, smoking as well as exogenous factors like diet, infection, stress are related to the onset and clinical manifestations of BD. DNA methylation refers to a major epigenetic element which influences gene activities with catalyzing DNA using a set of DNA methyltransferases (Dnmts). DNA methylation status of many genes in patients with BD is different from that of healthy people. For example, cytoskeletal gene, Human Leukocyte Antigen (HLA) loci, Long interspersed nuclear element (LINE-1), and Arthrobacter luteus (Alu) repetitive sequences are different in the DNA methylation status in patients with BD and healthy controls. In this paper we reviewed, according to previous studies, the mechanisms of epigenetic, the epigenetic factors involved in the BD, and especially the effect of DNA methylation in the Behcet’s disease. Future studies are needed to identify the capability of specific DNA methylation alterations in BD in order to predict disease manifestations, medical course, and response to treatment.